2022
DOI: 10.3390/jcm11206062
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Prevention and Clinical Treatment of Allergic Rhinitis: More Understanding, Better Patient Care

Abstract: Allergic rhinitis (AR) is a noninfectious inflammatory disease of the nasal mucosa mediated by IgE after atopic individuals are exposed to inhaled allergens and involving a variety of immune cells and cytokines [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our results are consistent with previous research on the differences in prevalence according to sex. AR prevalence were higher in males in comparison to females .Differences in condition prevalence is explained by higher levels of endogenous sex steroids hormones with increased Th2 response in women, whereas in men, testosterone works by suppressing the Th2 response Age distribution of our study showed that most people were in the age range of 30-37 years, and this is relabel with another reviews like Yang Liu,et al (2022) [28]who said that the peak of prevalence of allergic rhinitis with regard to age gradually.…”
Section: Discussionsupporting
confidence: 77%
“…Our results are consistent with previous research on the differences in prevalence according to sex. AR prevalence were higher in males in comparison to females .Differences in condition prevalence is explained by higher levels of endogenous sex steroids hormones with increased Th2 response in women, whereas in men, testosterone works by suppressing the Th2 response Age distribution of our study showed that most people were in the age range of 30-37 years, and this is relabel with another reviews like Yang Liu,et al (2022) [28]who said that the peak of prevalence of allergic rhinitis with regard to age gradually.…”
Section: Discussionsupporting
confidence: 77%
“…Low-and middle-income countries are experiencing high rise in cases of AR and it ranges from 1.0% to 54.5%. The prevalence increases by age as in children upto 3 years of age , it is 5%, in age group of 6-7 years of age , it is 8.5% and 14.6% in 13-14 year-olds, and rises to 11.8% to 46% in people aged 20-44 years old people [3] .…”
Section: Epidemiologymentioning
confidence: 95%
“…Providing a hygienic environment to children in their early life is also a risk factor as the child does not get exposed to these allergens. A positive family history of atopy and allergic disease is a strong predisposing factor [3,5] If one parent is suffering with allergic diathesis, chances of the offspring to be affected is 20 % and it rises to 47 % if both the parents are affected. [1]…”
Section: Predisposing Factors and Etiologymentioning
confidence: 99%
“…Allergic rhinitis is a common disease, which is becoming an increasingly serious global problem related to health, medicine, and economics. High-income countries show a prevalence of up to 50%, making it one of the most common chronic conditions, while the prevalence is comparatively low in low- and middle-income countries, despite the fact that it is steadily rising in these nations ( Bousquet et al, 2020 ; Liu and Liu, 2022 ). In Europe, over the last 3 decades, there has been a gradual increase from 19% to 32% of Danish adults suffering from allergic rhinitis ( Leth-Moller et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%